2001
DOI: 10.1046/j.1365-2648.2001.01797.x
|View full text |Cite
|
Sign up to set email alerts
|

A measure of patient empowerment in hospital environments catering for older people

Abstract: The PES is offered as a valid and reliable measure of empowerment and disempowerment in hospital settings catering for older people. It enables the identification of environments which place patients at risk of becoming dependent, or alternatively facilitate increasing independence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 35 publications
(35 reference statements)
2
78
0
3
Order By: Relevance
“…Seventeen definitions (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) (Chart 1) and seven dimensions (9,14,(24)(25)(26)(27)(28) of empowerment (Chart 2), and 10 empowerment measures (9,13,24,(29)(30)(31)(32)(33)(34)(35) (Chart 3) were selected. The analysis showed that the concept of empowerment has been broadly used in the health sciences field, especially over the last 10 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seventeen definitions (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) (Chart 1) and seven dimensions (9,14,(24)(25)(26)(27)(28) of empowerment (Chart 2), and 10 empowerment measures (9,13,24,(29)(30)(31)(32)(33)(34)(35) (Chart 3) were selected. The analysis showed that the concept of empowerment has been broadly used in the health sciences field, especially over the last 10 years.…”
Section: Resultsmentioning
confidence: 99%
“…Faulkner, 2001 (30) Patient Activation Measure (PAM) Generic Skills, knowledge, and beliefs needed by patients to self-manage, collaborate with healthcare providers and maintain their health.…”
Section: Empowerment Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Il importe de distinguer les connotations plus positives par opposition aux attitudes axées sur les faiblesses, les déficits et le manque de valorisation de l'expérience de la clientèle. Ces prédispositions sont issues de recherches qui ont tenté d'opérationnaliser certains concepts reliés à l'habilitation et leurs instrumentations ont subi des tests de validation auprès d'utilisateurs de divers services Faulkner, 2001aFaulkner, , 2001bTrivette, Dunst, Boyd et Hamby, 1995). D'autres prédispositions proviennent de devis descriptifs qui incorporent d'une part la perspective des intervenantes et intervenants (McNaughton, 2000) et d'autre part celle de la clientèle (Falk-Rafael, 2001;Pooley, Gerrard, Hollis, Morton et Astbury, 2001;St-Cyr Tribble et al, 2003.…”
Section: Prédispositions Pour L'intervention Professionnelleunclassified